Analysis of Motor Educability Levels of Elementary School Students Based on Geographical Location and Physical Activity - Riza Sukma Fauzi; Didik Subhakti Prawira Raharja; Novita Mayangsari (Universitas Majalengka, 2023)
Aim from study this that is for knowing motor educability level of student’s school base in the area urban and rural with look activity normal physique done. motor educability measurements were used as part from method scouting talent Skills motion in create potential athlete. Study this is done at school base in rural and urban areas in the district Majalengka with study descriptive quantitative, sorting sample done with stratified random sampling. Research results show exists difference motor educability level seen based on location geography and activity physical. Research results this expected could Become reference for guides giftedness that can see from motor educability and giving ability opportunity for the kids for could develop anywhere he be, both in the city nor village.